2020
DOI: 10.1002/mar.21406
|View full text |Cite
|
Sign up to set email alerts
|

Fear Of Missing Out Scale: A self‐concept perspective

Abstract: Fear of missing out (FOMO) is an emerging topic in consumer psychology. However, the theoretical foundations of FOMO are underdeveloped and extant FOMO scales confine the construct to the context of social media. Without a theoretical foundation and a new FOMO scale, the future development of research on this promising phenomenon is limited. This article provides a new conceptualization of FOMO and a new FOMO scale. Using self‐concept theory, the authors propose that FOMO is an emotional response to perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(155 citation statements)
references
References 57 publications
5
99
0
7
Order By: Relevance
“…thus, they rushed to buy them [63,64]. This view is supported by Zhang et al [56], who found the effect of perceived scarcity on choice mediated by FOMO.…”
Section: Relationship Between Scarcity Fear Of Missing Out and Impulsive Purchasingmentioning
confidence: 76%
See 1 more Smart Citation
“…thus, they rushed to buy them [63,64]. This view is supported by Zhang et al [56], who found the effect of perceived scarcity on choice mediated by FOMO.…”
Section: Relationship Between Scarcity Fear Of Missing Out and Impulsive Purchasingmentioning
confidence: 76%
“…Generally, fear of missing out (FOMO) is described as an emotion [54][55][56]. It is the consumer's anxiety about missing a chance or experience that others are having [1,57].…”
Section: Relationship Between Scarcity Fear Of Missing Out and Impulsive Purchasingmentioning
confidence: 99%
“…In addition to deriving satisfaction from feeling unique and special (Snyder, 1992), consuming scarce products may also help consumers to gain social status (Gierl & Hüttl, 2010) and appeal to their desire for exclusivity and power (Kim, 2018). Scarcity also elicits a fear of missing out (FOMO)-an uneasy feeling associated with being socially excluded from desired experiences (Zhang et al, 2020). Missing out on consumption experiences can therefore become a threat to the self-concept (Zhang et al, 2020).…”
Section: Scarcity Appealsmentioning
confidence: 99%
“…Subsequently, Alt (2015) [8], based on Przybylski's FoMO scale, developed a 10-item FoMO scale consisting of three dimensions (i.e., social media engagement, news information engagement, and commercial information engagement). More recently, Zhang et al (2020) [9] developed of 10 an 8-item scale consisting of two dimensions (i.e., personal and social FoMO). To measure some specific kinds of FoMO, Wegmann et al (2017) [10] developed a 12-item and twodimensional scale, assessing trait-FoMO and state-FoMO.…”
Section: Introductionmentioning
confidence: 99%